DISEASES OF CUCUMBERS GROWN IN GREENHOUSES AND MEASURES TO COMBAT THEM - Khalmuminova Gulchehra Kulmuminovna; Muhammadiyeva Munisa Xudoyberdi kizi (Journal Park Publishing, 2025)
This article covers the main diseases of cucumber plants grown in greenhouses, their causes and development conditions. In particular, the symptoms of such common diseases as Fusarium, Cladasporiosis (brown spot, olive mold, and squid disease) are analyzed in detail. Also, modern methods of preventing and combating diseases - agrotechnical prevention, the effectiveness of biological and chemical protection measures - are considered on a scientific basis. The article provides practical recommendations for ensuring stable yields in greenhouses, maintaining plant health, and growing environmentally friendly products.
Keywords: Greenhouse, сucumber, Fusarium, brown spot, olive mold, squid, Plant, Cladosporiosis, protection, control.